Dasar Pertimbangan Hakim Dalam Menjatuhkan Pidana Bersyarat Kepada Anak Pelaku Yang Menyebabkan Kematian - Giovani, Eldytha; Sudarti, Elly; Rakhmawati, Dessy (PAMPAS: Journal of Criminal Law, 2024)
This study aims to analyze and find out the basis and reasons for the panel of judges to impose criminal conditional on children who are perpetrators of abuse that cause death. The role of the authorized judge in imposing the sentence must go through various considerations. In verdict No. 12/Pid.sus-Anak/2021/PN Jmb it pertains to a severe assault case where the victim died as a result of the juvenile's delinquent behavior. This study uses a normative juridical method. The findings of this research reveal that the imposition of criminal conditional on children who are in confront with the law because judges is primarily based on sociological considerations. Sociological considerations encompass aggravating and mitigating factors, which the judge is obliged to include in the verdict according to Article 197, paragraph (1) of the Indonesian Criminal Procedure Code. The main reason for the panel of judges to impose a suspended sentence is not for retribution purposes but to provide an opportunity for the juvenile to reintegrate into society and become a better individual, hence the child is given a criminal conditional with the general conditions of probation for 10 (ten) months and specific conditions that must be fullfilled in accordance with Article 14 of the Indonesian Criminal Code and this case adhered to the guidelines of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System.